Improving English as a foreign language learners’ vocabulary and reading comprehension through crossword-assisted teaching - Yang, Yu-Chi (English Education Department, Universitas Islam Indonesia, 2024)
Numerous studies have demonstrated the effectiveness of crossword-assisted teaching for English as a foreign language (EFL) instruction. The present study evaluated the effectiveness of this technique in the Chinese-speaking EFL environment. Two cohorts of junior college students participated in this study. Both groups completed a vocabulary and reading skill pretest, which revealed no significant differences between the groups. For convenience, a larger cohort of 34 students was designated as the experimental group, and a smaller cohort of 32 students was designated as the control group. During the study, crossword-solving tasks and quizzes were integrated into the instruction provided to the experimental group, whereas traditional lecture-based instruction was provided to the control group. After the study, both groups underwent the same posttest. The experimental group significantly outperformed the control group in both vocabulary knowledge and reading comprehension. Additionally, the experimental group students’ responses to a learning attitudes questionnaire indicated their favorable perceptions of the use of crosswords in instruction. Therefore, this study verified the effectiveness of crossword puzzles in a non-Western linguistic learning environment, reinforcing the value of crosswords for EFL teaching.